Рассказчица: роман / Джоди Пиколт - Пиколт Джоди (Азбука, 2022)
Экземпляры: ф.18 (20240530) / Инвентарный номер: 4871 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: П 32 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44